True awareness of mental health remains in the shadow: an exploratory study on implementing mental health support in the workplace - Maninder Singh; P. S. James; Subramania Raju Rajasulochana; Gurch Randhawa (Cogent Psychology)
Mental health in the workplace is critical for employee engagement, productivity, and profitability. In India, only 0.09% of the 1.1 million registered companies have implemented Employee Assistance Programs (EAPs) for providing mental health support. This study leverages the Socio-Ecological Model (SEM) framework to examine the multi-layered dimensions impacting the implementation of mental health activities in the corporate sector in emerging economies, such as India. For a qualitative study, interviews were conducted with thirty-six industry experts representing diverse sectors to glean insights into the implementation of EAPs. Our analysis indicates that while the advantages of EAPs in early detection, proactive support, and mental well-being are widely recognized in the selected Indian corporate environments, the implementation of EAPs is restricted by the cultural-specific barriers, as well as quantitative measure of ROI, among other factors. Our findings will inform practitioners and policymakers in designing tailored strategies to encourage successful EAP implementation in the Indian corporate sector.